Genetic Polymorphism of SCD1 Gene of Holstein-Friesian Cows in Indonesia - Ari Sulistyo Wulandari; HD Rahayu; SD Volkandari; N Herlina; S Anwar; Y Irnidayanti (Jurnal Ilmu Ternak dan Veteriner, 2019)
Stearoyl-Coenzyme A desaturase 1 (SCD1) belongs to the fatty acid family of desaturases. In lactating ruminants, the SCD1 protein is highly expressed in the mammary gland and is relevant for the fatty acid composition of milk and dairy products. Polymorphism of SCD1 gene in Holstein-Friesian (HF) cows could be used as a basis of molecular selection of cattle in order to increase their productivity. The aim of this study was to investigate the polymorphism of SCD1 gene of Holstein-Friesian cows in Indonesia. A total of 162 blood samples of HF cows were collected from four different locations i.e. Bogor, Sukabumi, Tasikmalaya and Enrekang districts. Genotyping of SCD1 gene used PCR-RFLP method with NcoI restriction enzyme. The result showed that three genotypes (AA, AV and VV) and two alleles (A and V) have successfully found and polymorphic. A allele was dominant in all populations (0.63) and in Hardy Weinberg Equilibrium. The highest A allele was found in Sukabumi (0.78) and the lowest was in Bogor (0.55). Heterozigosity observed and expected reached 0.471 and 0.470, respectively. In conclusion, genetic polymorphism was found in all population with dominant of A allele. This finding can be used as a early genetic information of Holstein-Friesian cattle in Indonesia and to build breeding strategy for improving of productivity especially improving of healthy fat milk.